ANALISIS RESEPSI KHALAYAK TERHADAP ACARA TALKSHOW DI TENGAH PANDEMI VIRUS CORONA : Studi Deskriptif Pemirsa Televisi Dr. Oz Indonesia TransTV - Syarifah Usma (2021)
In the midst of a pandemic virus outbreak that is happening in the world, including in Indonesia today, health information through various mass media platforms is needed, including television media. With the implementation of self immunity and physical distancing at this time, health information conveyed by television shows is expected to be able to handle health problems independently at home. One of the television shows that aired on health information was Dr. talkshow Oz Indonesia. The health information is delivered and discussed directly by doctors and health experts. Therefore, the talk show Dr. Oz Indonesia is an interesting program to study, because the program material presented does emphasize aspects of health information but is packaged attractively and entertaining. By using reception analysis, researchers try to find out how audiences interpret the talk show Dr. Oz Indonesia towards their need for health information. The results showed that the talk show Dr. Oz Indonesia is interpreted positively by the public as a learning event for health science.